O impacto de condições sociais e econômicas na vida de mulheres em situação de prisão no Estado da Paraíba: um saber necessário para a elaboração de políticas públicas de saúde - Souza, Jackeline Abilio de (2019)
The right to health care to women in prison, although established, has not been answered in the environment of the prison system, to the health needs of this population. One of the reasons for this gap refers to the absence of public health policies, specific to this group, which address the issues of gender and ethnic/racial, social and economic differences. The different social and economic conditions and gender issues have an impact on health. It derives the relevance of the production of knowledge on the impact of these conditions in the life of the population in focus, for, on the basis of gender perspective, can subsidize the making and implementation of policies that contribute concretely to the attention of the health needs of women in prison. In this sense, the study had the intention to understand the impact of social and economic conditions on the lives of women under situation of prison in the State of Paraiba. The search had quantitative and qualitative approach and involved the inclusion of 210 women in prison in the State of Paraiba, who were in a closed regimen and over 18 years old. The data collection was performed after the pilot study, between May and August 2017, through workshops. The quantitative survey was performed by means of structured questionnaires that contained the variables of the study. A structured guide guided the production of the qualitative material. For the quantitative data analysis, there was used the Analysis of Groupings with the Software R, being defined four groups of women, whose interpretation of the social and economic profiles was subsidized through the Multinomial Test, based on the Chi-square statistics. According to the analysis: group 1 had income and own household; group 2 received income, had rented homes and precedence from different city from the location of the prison unit; the group 3 had not received income and had procedure from a different city from the location of the penal colony; and the group 4 did not receive income, had rented homes and was coming from the same city of location of the prison unit. The qualitative approach, which had as support the Discourse Analysis, allowed to reveal the impact of lack of income for economic autonomy and for the keep of essential conditions of life in prison and for the contribution to the livelihood. The distance between the female prison and the place of residence, (variable origin) represented an impact on the social and material support from the families to women. The management of the quantitative and qualitative analysis, using the perspective of gender, revealed the impact of those conditions in the lives of women in prison in the State of Paraiba, allowing to raise the health needs specific to each group. To engender health needs, the impact of social and economic conditions in the lives of women in prison situation needs to be considered in the decision-making process on the making of public health policies in the State of Paraiba.